RACE, ETHINICITY, GENDER, RELEVANCE, POLITICS, AND WHAT YOU TEACH. (Revista Apotheke, 2017)
Tradução do capítulo I do Livro: JAFFE, Nick; BARNISKIS, Becca & COX, Barbara Hackett. Teaching Artist Handbook, V. I: Tools, Techniques and Ideas. Chicago: Columbia College Chicago Press, 2013, p. 16-27. Tradução livre: Juliano Siqueira, doutorando no PPGAV/UDESC